Inovasi Furniture Berbahan Plywood Finishing High Pressure Laminate Sebagai Pendukung Pertumbuhan Properti di Desa Saba - Yogi Kertayasa, I kadek; Muka, I Ketut; Suparta, I Made (Pusat Penerbitan LPPM ISI Bali, 2025)
This study discusses innovation in the design and production process of furniture made from plywood with a High Pressure Laminate (HPL) finish, developed as a solution to support the growth of the property sector in Saba Village, Gianyar Regency, Bali. Along with the increasing development of residential properties, villas, and tourism-supporting facilities in the area, the demand for furniture with high quality, appealing aesthetics, durability, and cost efficiency continues to rise. This research employs a descriptive qualitative method through field studies, observations, interviews with property industry stakeholders and local artisans, as well as product prototyping experiments. Plywood was selected as the primary material due to its advantages, including lightweight properties, stable structural strength, ease of fabrication, and environmentally friendly characteristics compared to solid wood. Meanwhile, the application of HPL finishing adds value by providing resistance to scratches, heat, and humidity, as well as allowing the exploration of various modern and elegant patterns and colors. The design process was carried out by considering ergonomic principles, space efficiency, and harmony with the tropical architectural character of Saba Village.The results indicate that the use of plywood with HPL finishing produces furniture that is not only functional and aesthetically appealing but also competitive in terms of production costs. This innovation has the potential to strengthen the competitiveness of the local creative industry, encourage collaboration between artisans and property developers, and contribute to economic growth based on design and tourism in Saba Village